NARRATIVE RESEARCH. SECONDARY EDUCATION INCLUSIVE AND SCHOOL TRAJECTORIES STUDENTS WITH DISABILITIES, DISADVANTAGED EDUCATIONAL PROCESS - Beatriz Margarita Celada (Universidad Nacional del Nordeste, 2019)
In the last 10 years, a journey has been made from research projects. They have followed a thematic line exploring alternative educational experiences as proposals for the transformation of inclusive practices in secondary schools. These are meant for students with disabilities and / or disadvantaged educational process. Thus, we have focused our attention on the school narratives of the actors involved in the challenge of inclusive education. The essential purpose that we set ourselves is to develop strategies of collaborative research, and to share reflection with the intention of investigating practices that promote an educational and social change. In this framework, we try to denaturalize everyday conceptions that are rooted in the subjectivities of teachers and students. For this, we try to accompany the construction of work devices as support configurations to favor the school trajectory of any student. We will priorize, in this stage of our investigation, the voices of the students as subjects of the investigation, which are understood both collectively and individually. We will also accompany promoting an active participation in learning, building democratic alternatives in a framework of collective cooperative work. Our aim is to put into words what worries, disturbs them, recognizing the political dimension of our ways of living together in family, at school, in the streets. The voices will be incorporated from different strategies and resources. Since in the narrative methodology the investigacion does not depend on the collection of a single type of "data".